2013
DOI: 10.1071/py11146
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of primary health care physician managers toward research: a pre-experimental study

Abstract: Research in primary health care (PHC) is underdeveloped and scarce, especially in developing countries. It is important to understand the attitudes and aspirations of PHC physicians for the promotion of research. The aim of this study was to determine the attitudes of PHC physician managers toward research in Qassim province and to identify barriers that impede performing research in the PHC system. The study was based on social cognitive theory framework, and was pre-experimental with a 'one-group pre-test-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…7 However, similar to our findings, majority of the previous studies conducted across the health professionals have reported overall good attitude towards medical research. [4][5][6][7][14][15][16][17] The proportion of correct responses in different knowledge items related to research methodology ranged from 14% (knowledge item related to reference management software) to 55% (knowledge item related to consent). We didn't find a significant relationship with knowledge and gender, however; some have reported a significant association of gender with knowledge, attitude and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, similar to our findings, majority of the previous studies conducted across the health professionals have reported overall good attitude towards medical research. [4][5][6][7][14][15][16][17] The proportion of correct responses in different knowledge items related to research methodology ranged from 14% (knowledge item related to reference management software) to 55% (knowledge item related to consent). We didn't find a significant relationship with knowledge and gender, however; some have reported a significant association of gender with knowledge, attitude and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Having good attitude along with low knowledge have also been reported by various other studies. [4][5][6][15][16][17] Interestingly the knowledge items were not found to be statistically significantly different among classes of health professionals, however; it was higher among physicians. Among primary care physicians, a significantly higher level of research participation has been reported among family medicine specialist as compared to general practitioners.…”
Section: Discussionmentioning
confidence: 99%